Experimental Studies on Convective Heat Transfer Performance Using Ethylene Glycol Based Nanofluid - N. A., Usri; Azmi, W. H.; R., Mamat; Khamisah, Abdul Hamid; G., Najafi (2015)
Nanofluid has become a potential candidate as thermal fluid in designing optimized heat transfer system. Thus, in order to understand convective heat transfer of nanofluid requires experimental approaches. The paper presented thermophysical properties and convective heat transfer performance using water/ethylene glycol based nanofluid. Preparation of nanofluids is conducted in the laboratory using two step method for Aluminium Oxide (Al2O3) in 40:60 volumetric ratio (water: ethylene glycol) mixture. The investigation were conducted using 0.2 %, 0.4 % and 0.6 % volume concentration in a constant heat flux condition at working temperature of 50 oC within various Reynolds number. It was found that the convective heat transfer of the selected nanofluid enhanced with increased concentration compare to its base fluid. The highest heat transfer enhancement of Al2O3 nanofluid is found using 0.6 % volume concentration by 17.8 % higher than based liquid